Speech and computer : 18th International Conference, SPECOM 2016, Budapest, Hungary, August 23-27, 2016, Proceedings /: 18th International Conference, SPECOM 2016, Budapest, Hungary, August 23-27, 2016, Proceedings. (2016) - Unknown
No abstract available